Financial Liberalization and operational efficiency in the Financial system of Sri Lanka - Karunanithy, K. (Eastern University, Sri Lanka, 2004)
This study attempts to evaluate the operational efficiency of Sri Lankan financial system during post liberalization period. Indicators such as assets, deposits and loan concentration in the banking industry, trends of interest rates, employee costs, reserve requirements, return on assets (ROA) are used to capture the effects of financial reforms on the operational efficiency of the financial system. These indicators revealed high concentration in the banking system, less competition and high cost of banking. It is also evident that banking system as a whole is not very stable. All these lead to the conclusion of partial success of the financial reforms implemented during the post liberalization period.